Malaysia’s Experience with the Small and Medium Sized Enterprises Masterplan : Lessons Learned - World Bank Group (World Bank, Malaysia, 2020)
Productivity-enhancing measures play a pivotal role in Malaysia’s aspirations of becoming a high-income economy. Malaysia has enjoyed an impressive growth performance over the past few decades, with growth rates of at least 7 percent per year for more than 25 consecutive years. However, with the rise of other emerging economies, notably China and India, Malaysia has faced challenges in pivoting away from a ‘low-cost, high-volume’ strategy towards a ‘high-value’ one. Small and medium-sized enterprises (SMEs) are a crucial component of Malaysia’s strategy to become a high-income nation. As SMEs account for all but 1.5 percent of firms and the bulk of production and employment, they are central to Malaysia’s objective of becoming a high-income economy. SMEs form the bedrock of the private sector and innovation and can contribute to growth by supplying multinationals or accessing international markets directly. Despite their critical importance, the share of Malaysian SMEs in GDP (32 percent) and total exports (16 percent) was far lower than competitors in 2010. At the time of preparation of the Masterplan, the export share was more than 20 percent lower than that in countries such as the Philippines, Hong Kong, Taiwan and even the US, and there was also scope for greater sectoral and geographical diversification. It was recognized that specific policies to enable favorable conditions for SMEs to flourish were needed so that they can easily expand into fast-growing markets and increase the production of knowledge- and innovation-based products and services.